FAKTOR-FAKTOR DETERMINAN YANG BERHUBUNGAN DENGAN KEPADULIAN PESERTA DIDIK SMP CENDANA PEKANBARU TERHADAP LINGKUNGAN SEKOLAH - Siregar, Sofyan Husein (Jurnal Kajian Lingkungan, 2013)
Formal environmental education can be obtained at the school, because the school which isinvestment values about the environment in order to enhance students´ awareness of theenvironment. This needs to be inculcated in the students because they are the youngergeneration as a determinant of the future of the nation. Formulation of the problem in thisstudy is (1) whether there is a relationship between parental employment and livingenvironment with concern for the living environment (2) Which factor is most associatedwith concern of Students Cendana Junior High School Pekanbaru to school environmentbased on parental employment and living environment.Concern for the environment isinfluenced by various aspects such as knowledge, attitudes and responsibilities. Researchwas conducted in Pekanbaru Cendana Junior high school through survey methods, arequired primary data were obtained from leaners by questionnaire and secondary datahave been available at the school. Data analysis used chi-square tests and multipleregression analysis with helping of SPSS program.The results confirm that the studentscaring view of working parents whether they are CPI and non-CPI. Their parents who arenot CPI employees care more than CPI employees . While the students caring view ofliving environment in the complex and the outside of the CPI complex, the students who liveoutside of the CPI complex are more concerned than they live in the CPI complex. Comparethe children of CPI employees who live in complex and outside the complex, the children ofCPI employees who live outside the complex more concerned than they live in the complex.Then from the three variables that concern affecting are knowledge, attitude andresponsibility, the more dominant influence learners concern is the aspect of knowledge.